MILLING FORCE MODELING BASED ON EQUIVALENT TURNING FORCE AND OBLIQUE CUTTING FORCE MODEL (MT) - WU MingZhou; ZHANG GuangPeng; LIU MoHan; GOU JianFeng; ZHANG Peng (Jixie qiangdu)
The accuracy of traditional milling force prediction model is low, and it is difficult to provide effective support for the reasonable selection of process parameters in practical production, by synthetically considering the equivalent turning force model of working angle, cutting edge arc and radius of tool tip arc, in this model, the actual turning tool is equivalent to the ideal turning tool model to identify the material constant, the chip flow angle and the average friction angle in the material constitutive equation, according to the oblique cutting model, the shear stress on the main shear plane and the F0 vector of the unit cutting force at different cutting speeds are calculated, thus the instantaneous cutting force on the front face of the end mill can be calculated, the three-dimensional cutting force of end mill in X-Y-Z coordinate system is obtained by coordinate transformation. The prediction of the cutting force model is verified by simulation and experiment.